Reality checks in Mozambique - Building better understanding of the dynamics of poverty and well-being. Year Four, 2014, sub-report, District of Lago - Tvedten, Inge; Paulo, Margarida; José, Barnabé; Putile, Beatriz (ORGUT Consulting AB, 2014)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 4th Sub-Report from the District of Lago, focusing on the private sector/entrepreneurship. An Annual Report is produced each year to summarise the findings and conclusions from the three sub-reports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Hunger Revolts and Citizen Strikes: Popular Protests in Mozambique, 2008-2012 - Brito, Luis de; Chaimite, Egídio; Pereira, Crescêncio; Posse, Lúcio; Sambo, Michael; Shankland, Alex (Institute of Development Studies/Instituto de Estudos Sociais e Economicos, 2014)
In February 2008 and September 2010, the cities of Maputo and Matola were the scene of violent protests against the rise in the cost of living, undertaken by groups of ordinary citizens. Immediately afterwards, these protests were replicated in some other Mozambican cities, but on a much smaller scale, and they were quickly brought under control by the police. In November 2012, a new protest was set in motion, but immediate repressive action by the police (which in recent years has been greatly strengthened in men and material) in the key places where people were gathering prevented the violence from spreading, although it did not prevent the near total paralysis of activity in greater Maputo for a day and a half.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Reformas de descentralização e serviços públicos agrários em Moçambique: Porquê os desafios persistem? - Forquilha, Salvador (IDeIAS, 2014)
Nos anos 1980, vários países da África subsaariana iniciaram um conjunto de reformas ligadas ao sector público visando, entre outros objectivos, fazer face à crise do Estado, que se manifestava essencialmente em duas dimensões, nomeadamente regulação política e provisão de serviços públicos. Desde então, assistiu-se a três gerações de reformas do sector público (Kiragu, 2002; Crook, 2010). A primeira geração vai dos meados dos anos 1980 aos meados dos anos 1990, com enfoque nos Planos de Ajustamento Estrutural; A segunda geração destacou-se nos meados dos anos 1990, com uma forte componente de assistência técnica aos programas das reformas; Finalmente, a terceira geração das reformas inicia nos finais dos anos 1990 e começos dos anos 2000, marcada pela ligação das reformas com as Estratégias de Redução da Pobreza (no caso de Moçambique os PARPAs e o PARP) e um enfoque na questão da descentralização e melhoria de serviços públicos. Que resultados estas reformas trouxeram em termos de provisão de serviços públicos?
Keywords: G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; decentralization / descentralização; ⛔ No DOI found

Socio-economic and Community Health Baseline - Anadarko Mozambique (ExxonMobil, 2014)
This chapter outlines the socio-economic and health baseline of areas (both onshore and offshore) potentially affected by the Project. The chapter is structured into a number of sections, as follows: • Sections 9.2 and 9.3 provide a summary of the baseline and sources of information used to compile the baseline, respectively. • Section 9.4 defines the Project Area of Influence, providing both an overview of the geographic characteristics as well as the respective administrative divisions and governance structures. • Sections 9.5 to 9.7 provide an overview of Cabo Delgado Province (an important part of the Area of Indirect Influence) and aims to set the broader social, health and economic context in which the Project will be located. • Sections 9.8 to 9.14 provide a description of the social, health and economic characteristics of the Area of Direct Influence, which includes Palma District and the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.15 provides a description of the cultural and religious profile of the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.16 provides an overview of perceptions and expectations about the Project. • Section 9.17 provides an understanding of the shipping movements and types of vessels used within the Study Area. • Section 9.18 details the archaeology and cultural heritage baseline of the Afungi Project Site, based on both primary and secondary data.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; health / saúde; poverty / pobreza

Guião de consulta e participação da sociedade civil e cidadãos no funcionamento dos conselhos consultivos locais - Monjane, Celso; Salimo, Padil (MASC, 2014)
O presente guião é um instrumento que tem em vista dotar as OSC e cidadãos de modo geral, de conhecimentos sobre o funcionamento dos Conselhos Consultivos Locais (CCLs) de maneira a facilitar a sua participação e a alargar as suas intervenções na área de monitoria e advocacia da governação a nível distrital. Estão apresentados neste guião, os elementos que permitem perceber a organização, a estrutura, funções, e responsabilidades dos Conselhos Consultivos Locais, como eles funcionam, as oportunidades existentes para a participação das OSC e cidadãos de um modo geral na articulação com os Conselhos Locais por forma a estimular diálogo e contribuir na melhoria da sua influência na tomada de decisões e na melhorias na prestação de serviços às comunidades a nível dos distritos pelos governos distritais. O guião está estruturado em cinco secções. A primeira secção, apresenta o contexto, objectivos e a metodologia usada na sua elaboração; a segunda secção, procura explicar os principais elementos sobre a participação e consulta comunitárias, as formas de organização das comunidades locais para a participação comunitária, e a importância da participação e consulta comunitária, bem como uma explicação sobre como a consulta e a participação é feita a nível distrital. A terceira secção, apresenta detalhadamente aspectos sobre funcionamento, tarefas e estratégias de trabalho, bem como formas de prestação de contas. A quarta secção, fala sobre os mecanismos de escolha dos membros dos Conselhos Consultivos Locais, número de membros e direitos e deveres que eles possuem. A quinta secção, fornece algumas bases sobre como a sociedade civil e cidadãos podem contribuir para o fortalecimento dos CCLs, bem como, as estratégias para incrementar mecanismos de monitoria e advocacia.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; citizenship & participation / cidadania e participação; collaboration / colaboração; governance / governação; government policy / politica governamental

Displacement and Dispossession Through Land Grabbing in Mozambique: The Limits of International and National Legal Instruments - Twomey, Hannah (Refugee Studies Centre (RSC), 2014)
This working paper examines the limitations of international and national law to address displacement and dispossession from land grabs within the case study of Mozambique. The main question that I seek to answer is: What limits international and national law in addressing displacement and dispossession due to land grabs in Mozambique? I will argue that the limits of law to address displacement and dispossession are not due to a lack of institutionalising international good governance norms into domestic-level legal frameworks. Nor can the limits be attributed to state incapacity. Rather, the limits of law lie within the norm implementation process, wherein norms are conditioned by the local Mozambican governance context to serve domestic interests
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; Law - Rule of Law / Law - Estado de Direito; governance / governação; land governance / gestão de terra

Guião de Consultas Comunitárias - Tankar, Issufo (Centro Terra Viva (CTV), 2014)
Em 2009, o Centro Terra Viva (CTV) publicou o Guião de Consultas Comunitárias, como parte do seu esforço em melhorar a aplicação da legislação sobre terras e outros recursos naturais. O guião resultou de várias pesquisas de campo realizadas pelo CTV e outras organizações que trabalham na área de Terras. No entanto, a aprovação do Decreto n° 43/2012 de 10 de Outubro, seguida do Diploma Ministerial n° 158/2011 de 15 de Junho, uma parte significativa do Guião ficou ultrapassada. Por outro lado, foram aprovadas directrizes pelo Fórum de Consulta sobre a Terra que são relacionadas a este tema. Deste modo, e como forma de facilitar a interpretação e aplicação do quadro legal sobre consultas comunitárias, o Centro Terra Viva, produziu este guião de consultas comunitárias destinado às comunidades, técnicos do Estado, técnicos de ONG’s e todos actores que trabalham na área de Terras.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Gender in Political Economy Analysis - Browne, Evie (GSDRC, University of Birmingham, 2014)
This report provides a brief examination of how and where gender analysis is incorporated into Political Economy Analysis (PEA). An initial review of the literature indicates that gender is not systematically included in PEA. This was also conveyed by a number of experts consulted for this report, who stated that few if any PEAs to their knowledge had included a gender analysis, with the issue usually treated only in passing. The report nevertheless highlights the existing examples of gender-oriented analytical questions used in common PEA tools. It also identifies areas of overlap between gender and political economy analysis.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); gender / género

Mozambique land policy development case study - Locke, Anna (Overseas Development Institute, 2014)
This case study has been produced in response to a request made to the Evidence on Demand Helpdesk. The objective of the request was to provide a detailed case study on the evolution of land policy in Mozambique and provide the reader with insights into what is viewed as one of Africa’s most progressive land laws, recognising multiple forms of tenure. Mozambique has experienced accelerated rates of growth over the past decade, averaging 7.2% per year, with projected growth rates of over 8%. However, this high growth rate has failed to translate into significant reductions in poverty and inequality has increased in almost all parts of the country. While growth has been driven by capital-intensive projects, mainly in the extractives sector, agriculture is seen as an important foundation for economic development and there has been a high level of interest in acquiring large tracts of land for investment over the past six years. Mozambique is one the most land-abundant countries in Africa, with around 80 million hectares (has). Currently, only five million hectares are cultivated, mainly by smallholders under rain-fed, traditional systems, and only 3-5% of landholdings are formally registered.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra

Abordagens para promover responsabilização social: revisão de algumas experiências - McGee, Rosie; Wanjiku Kelbert, Alexandra (Laboratório de Inovação do CEP - CEP - Cidadania e Participação, 2014)
O Programa Cidadania e Participação (CEP) (2013-2018) apoia os cidadãos na monitoria da qualidade de prestação de serviços de saúde e de educação em quatro províncias de Moçambique, assim como a advogar para a melhoria da qualidade desses serviços nos níveis distrital, provincial e nacional. O CEP pretende contribuir para: uma maior disponibilidade de informação relevante de modo a que os cidadãos tenham um melhor acesso e benefício dos serviços prestados pelo sector público; melhorar as capacidades dos cidadãos de avaliar a prestação de serviços e de se envolverem com os provedores de serviços de modo a melhorar a qualidade dos serviços de saúde e educação aos níveis primário e secundário; apoiar as organizações da sociedade civil a impulsionarem essas constatações nos processos de tomada de decisões a níveis mais altos.Este programa facilitará o diálogo entre cidadãos e comunidade por um lado, e os provedores de serviços por outro lado, para melhorar a qualidade dos serviços. Esta análise constitui uma parte da contribuição do IDS para o Output 5 do CEP (Output 5: ‘Aprendizagem e metodologias compartilhadas e aplicadas por outros actores do desenvolvimento’). Esta fornece uma visão geral de algumas das mais inovadoras experiências de responsabilização social e práticas de envolvimento dos cidadãos de vários contextos africanos, bem como internacionais, como forma de ajudar a aumentar o nível geral de interesse e consciencialização sobre práticas inovadoras de envolvimento dos cidadãos em Moçambique.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - portuguese / português; accountability / responsabilização; citizenship & participation / cidadania e participação

Perfil Do Distrito De Macomia Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Macomia; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação

Perfil Do Distrito De Pemba Metuge Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Pemba Metuge; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação; poverty / pobreza